2018
DOI: 10.1002/evl3.80
|View full text |Cite
|
Sign up to set email alerts
|

Lineages evolved under stronger sexual selection show superior ability to invade conspecific competitor populations

Abstract: Despite limitations on offspring production, almost all multicellular species use sex to reproduce. Sex gives rise to sexual selection, a widespread force operating through competition and choice within reproduction, however, it remains unclear whether sexual selection is beneficial for total lineage fitness, or if it acts as a constraint. Sexual selection could be a positive force because of selection on improved individual condition and purging of mutation load, summing into lineages with superior fitness. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…(1) = 0.78, p = .67, polyandry χ 2 (1) = 5.19, p = .07), indicating similar responses to the three different stresses conspecific competitors (Godwin et al, 2018). Here, we now demonstrate applied benefits of sexual selection for population and lineage fitness by revealing that an evolutionary history of enforced monogamy with low sexual selection weakens the ability of populations and lineages to cope with multiple interacting anthropogenic challenges through an extinction vortex.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…(1) = 0.78, p = .67, polyandry χ 2 (1) = 5.19, p = .07), indicating similar responses to the three different stresses conspecific competitors (Godwin et al, 2018). Here, we now demonstrate applied benefits of sexual selection for population and lineage fitness by revealing that an evolutionary history of enforced monogamy with low sexual selection weakens the ability of populations and lineages to cope with multiple interacting anthropogenic challenges through an extinction vortex.…”
Section: Discussionmentioning
confidence: 59%
“…Monogamous pairs were maintained and mated in containers containing 2 g flour medium, and polyandrous groups were maintained and mated in containers with 6 g flour medium, therefore allocating 1 g flour medium per adult throughout. After reproduction, adults were removed and eggs/larvae pooled from the multiple pairs or groups within each line, with the flour medium increased and equalized between regimes to 100 g and left to develop under standardized conditions until pupae were ready for the next generation (Godwin et al, 2018;Lumley et al, 2015).…”
Section: Experimental Evolution Under Varying Mating Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Prokop et al 2019 ). A population history (up to ten years) of experimentally applied, strong sexual selection has also been shown to improve the competitive ability of males and their sperm, and drive sperm morphology evolution (Michalczyk et al 2011 ; Demont et al 2014 ; Godwin et al 2017 ), increase conspecific population invasion success (Godwin et al 2018 ), enable population resilience to the extinction vortex (Godwin et al 2020 ), and increase the rate of pesticide resistance evolution (Jacomb et al 2016 ).…”
Section: Reproduction and Sexual Selectionmentioning
confidence: 99%
“…Experimental studies in this species have shown that founder effects have pronounced costs as a result of genetic and demographic effects and that colonising populations are able to rapidly adapt to novel environments (Szucs, Melbourne, Tuff, & Hufbauer, 2014; Szucs, Melbourne, Tuff, Weiss‐Lehman, & Hufbauer, 2017). Further, this species is promiscuous, and experimental evolution studies have shown that a history of strong sexual selection results in decreased risk of extinction under inbreeding and improved invasion into competitor populations (Godwin et al., 2018; Lumley et al., 2015). Moreover, matings and fertility often appear to fail in this species (Tyler & Tregenza, 2013), and there is some evidence to suggest that these costs are reduced when females mate multiply (Pai, Bennett, & Yan, 2005).…”
Section: Introductionmentioning
confidence: 99%